Integrating bulk and single-cell RNA sequencing data reveals the relationship between intratumor microbiome signature and host metabolic heterogeneity in breast cancer - Chen, Fangyue; Yang, Jun; Guo, Youxiang; Su, Dongwei; Sheng, Yuan; Wu, Yanmei (Frontiers in Immunology, 2023)
Nowadays, it has been recognized that gut microbiome can indirectly modulate cancer susceptibility or tumor progression. But it is not fully understood whether intratumor microbes are parasitic, symbiotic, or merely bystanders in breast cancer. Microbial metabolite plays a pivotal role in the interaction of host and microbe via regulating mitochondrial and other metabolic pathways. However, the relationship between tumor-resident microbiota and cancer metabolism is still an open question. In order to better understand the issue, we carried out bioinformatic analyses to explore the interplay between host and microbe in breast cancer. Here, we found that metabolic status of breast cancer cell was highly plastic and some microbial genera were significantly correlated with cancer metabolic activity. Two distinct clusters were identified based on microbial abundance and tumor metabolism data. Then, we used Scissor method to identify microbe-associated cell subpopulations from single-cell data. And dysregulation of metabolic pathway was observed among different cell types. Metabolism-related microbial scores were calculated to predict overall survival in patients with breast cancer. Furthermore, microbial abundance of specific genus was associated with the MAP3K1 and PIK3CA mutation due to possible microbe-mediated mutagenesis. It was remarkable that the infiltrating immune cell compositions, including memory B cells, resting memory CD4+ T cells, T follicular helper cells, regulatory T cells, and activated NK cells, were significantly associated with phylum-level diversity of metabolism-related intratumor microbes as indicated in mantel test analysis. And the mammary metabolism-related microbes were related to T cell exclusion and response to immunotherapy. Overall, the exploratory study shed light on the potential role of metabolism-related microbiome in breast cancer patients. And the promise of novel treatment will be realized by further investigation on microenvironmental metabolic disturbance in host and intratumor microbial cells.